Halal Politics Role in the Fight against Vote-Buying and Hoaxes - Septiadi, Muhammad Andi; Joharudin, Agus; Lestari, Nadia Ginan; Fajri, Rully Reinali; Khendra, Muhammad (Indonesian Journal of Halal Research, 2020)
During the election year, political candidates apply different strategies to win the election. Some candidates resort to spreading hoaxes and vote-buying. This phenomenon has become a trouble for the country as there will be severe repercussions. Halal politics is a new concept that needs to be studied. It aims to reduce or even eradicate hoax spreading and vote-buying. It also hopes to provide a further reference in political activities for both politicians and people generally. This study used qualitative literature study and thematic interpretation to collect data that are related to halal politics. The sources of the data are study results, Quran, and scholar Quran interpretation. The study concludes that halal politics implementation depends on heavily on people's active participation in preventing and stopping hoaxes and vote-buying. Furthermore, with the increase in society's political literacy, political candidates will change their strategy for the better.